Use of complementary and alternative medicine by patients with end-stage renal disease on haemodialysis in Trinidad: A descriptive study - Mandreker Bahall (BMC, 2017)
Abstract Background Despite the paucity of scientific evidence, complementary and alternative medicine (CAM) is widely used for the prevention and treatment of illness, holistic care, and counteracting the adverse effects of conventional medicine (CM). This study investigates the use of CAM by patients with end-stage renal disease (ESRD) on haemodialysis. Methods This quantitative study was conducted from November 1, 2014 to December 31, 2014 in the haemodialysis unit at San Fernando General Hospital (San Fernando, Trinidad). Face-to-face questionnaire-based interviews were held with101of 125 eligible patients (response rate, 80.5%) at the chairside during haemodialysis. The completed questionnaires were entered into a secure computer database. Data analysis included descriptive analysis, χ2 tests, and binary logistic regression analysis. Results A minority of the patients were CAM users (n = 19; 18.8%). All 19 CAM users took medicinal herbs, 78.9% (n = 15) used spiritual therapy, and 10.5% (n = 2) used alternative systems. Medicinal tea (n = 15; 78.9%), garlic (Allium sativum) (n = 17; 73.7%), and ginger (Zingiber officinale roscoe) (n = 13; 68.4%) were the most commonly used medicinal herbs. Seven (36.8%) patients used Chinese herbal medicines and 3 (15.8%) patients used Aloe vera. All CAM users were willing to use CAM without supervision or monitoring by their doctors while receiving CM. The use of CAM could not be predicted by age, sex, ethnicity, education, religion, marital status, or employment. Nearly all (98%) patients were satisfied with CAM. More than one-third (36.8%) of patients did not disclose their use of CAM to their doctors, who were generally indifferent to such therapy. Conclusions The use of CAM by patients with ESRD was relatively infrequent. All patients used medicinal herbs, most patients used spiritual therapy, and a minority of patients used alternative systems. Complementary and alternative medicine was primarily used for spiritual reasons and the likelihood of its use was influenced by family, friends, and other patients. Patients continued using CM with one or more CAM therapies without informing their healthcare providers, which is a major health risk.